Loss of IDH2 Accelerates Age-related Hearing Loss in Male Mice - Karessa White; Mi‐Jung Kim; Chul Ju Han; Hyo‐Jin Park; Dalian Ding; Kevin N. Boyd; Logan C. Walker; Paul J. Linser; Zaimary Meneses; Cole Slade; Jonathan J. Hirst; Katherine E. Santostefano; et al. (2018)
Abstract Isocitrate dehydrogenase (IDH) 2 participates in the TCA cycle and catalyzes the conversion of isocitrate to α-ketoglutarate and NADP + to NADPH. In the mitochondria, IDH2 also plays a key role in protecting mitochondrial components from oxidative stress by supplying NADPH to both glutathione reductase (GSR) and thioredoxin reductase 2 (TXNRD2). Here, we report that loss of Idh2 accelerates age-related hearing loss, the most common form of hearing impairment, in male mice. This was accompanied by increased oxidative DNA damage, increased apoptotic cell death, and profound loss of spiral ganglion neurons and hair cells in the cochlea of 24-month-old Idh2 −/− mice. In young male mice, loss of Idh2 resulted in decreased NADPH redox state and decreased activity of TXNRD2 in the mitochondria of the inner ear. In HEI-OC1 mouse inner ear cell lines, knockdown of Idh2 resulted in a decline in cell viability and mitochondrial oxygen consumption. This was accompanied by decreased NADPH redox state and decreased activity of TXNRD2 in the mitochondria of the HEI-OC1 cells. Therefore, IDH2 functions as the principal source of NADPH for the mitochondrial thioredoxin antioxidant defense and plays an essential role in protecting hair cells and neurons against oxidative stress in the cochlea of male mice.